PENGARUH LITERASI KEUANGAN TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT (Studi Kasus Kecamatan Unter Iwes) - Nining Sudiyarti; I Nyoman Sutama; Karina Aprilia (Jurnal Ekonomi & Bisnis, 2021)
This study aims to know the effect of financial literacy toward community welfare in the UnterIwes sub-district. The type of this study was quantitative. The data collection method used in this study was a questionnaire. The numbers of respondents of this study were 100 respondents. The analytical statistic tool to test the hypothesis was simple linear regression analysis with SPSS 16 and Microsoft Excel 2010. Based on the results of study and discussion to answer the hypothesis, based on the results of t-test obtained t-value> t-table (5,220 > 1,984) it means that H0 was rejected and Ha was accepted. Although the Financial Literacy variable (X) had an output coefficient of determination (R Square) of 0.218, the Financial Literacy variable (X) still had a value to effect the constant value of the Community Welfare variable (Y). So it can be concluded that there was effect between Financial Literacy and the Community Welfare.